Mapping Emotions: Exploring the Impact of the Aussie Farms Map. (August 2020) - Barnes, Ash; White, Rob
Counter-mapping refers to the public dissemination by activist groups of maps that visually document particular harms and offenders or sites of justice and prior ownership. Drawing upon green criminology, this article analyses the consequences of using counter-mapping as an activist tool. It examines how media framing of the Aussie Farms map is constructed around particularly polarizing narratives. This interactive map demonstrates the location and proliferation of animal agriculture and animal exploitation industries within Australia. Media framing has generated heated debate among Australian farmers and activists alike by inciting deeply emotional responses to the issues. We explore these common media narratives and their consequences for activists and tools such as counter-maps.